Dominica, priorities and prospects for development (World Bank Washington, D.C.US, 1985)
Reviews performance of the Dominica economy in the early 1980's. Examines performance of individual sectors such as agriculture and tourism and discusses development constraints and priorities. Describes the level and allocation of public and private sector investment noting areas of emphasis. Points out the main tasks ahead viz. to increase productivity in the traditional sectors; to continue to diversify the productive base of the economy and to improve the physical and supporting infrastructure.
DC